Placental Villous Vascularity is Decreased in Premature Infants with Bronchopulmonary Dysplasia-Associated Pulmonary Hypertension. (March 2016) - Yallapragada, Sushmita G.; Mestan, Karen K.; Palac, Hannah; Porta, Nicolas; Gotteiner, Nina; Hamvas, Aaron; Grobman, William; Ernst, Linda M.
The development of pulmonary hypertension (PH) is a serious complication of bronchopulmonary dysplasia (BPD) among infants born at extremely low gestational ages. Bronchopulmonary dysplasia-associated PH is characterized by persistent pulmonary vasoconstriction, progressive right heart dysfunction, and an increased risk of death. We have shown previously that certain placental vascular lesions are associated with BPD-associated PH. Further evaluation of the villous and vascular morphometry of these placentas is warranted. Using digital image analysis (DIA), we compared villous and vascular morphometric parameters of placentas from infants with and without BPD-associated PH. We conducted a case-control study of placentas from 14 infants born at ≤28 weeks' gestational age (GA). Cases with PH ( N = 7) and non-PH controls ( N = 7) were identified using echocardiogram screening at 36 weeks' corrected GA. Central parenchymal sections from each placenta were stained for CD31. Digital image analysis was used to measure vessel and villous capillary number, perimeter, diameter, and area. Mean villous vascularity (number of vessels per villus) was calculated for each patient. Mean vessel and villous number as well as area were similar between the two groups. Villous vascularity was decreased in placentas from infants who ultimately had PH disease compared to non-PH controls (5.5 ± 1.0 vs 7.1 ± 1.6; P < 0.05). Placental villous vascularity is decreased in infants with BPD-associated PH. Further studies should assess whether placental morphometric markers may allow clinicians to better predict BPD and provide earlier and more targeted management.